Computers in Cardiology, 2003 2003
DOI: 10.1109/cic.2003.1291141
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory response to passive and active changes in posture

Abstract: To understand the sequence of hemodynamic events elicited by active (stand-up) and passive (head-up tilt, HUT) changes in posture, we monitored heart rate and arterial blood pressure continuously in ten healthy volunteers at rest, during rapid tilts (7s' HUTover 2 secs), slow tilts (75" HUToverSOsecs), andstand tests. A marked initial transient dmp in mean arterial pressure (MAP) and increase in heart rate (HR) seen during rapid tilt, RZ and stand-up, SU, were absent during slow tilt, SZ While the magnitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…Our analysis of the heartbeat interval series from the subjects in the tilt-table study showed that the time courses of the mean R-R intervals and the heart rate series follow the well-documented patterns of cardiovascular response to orthostatic stress (7,16,25,26,46,50). Together, the instantaneous heart rate, instantaneous mean R-R interval, R-R standard deviation, and heart rate standard deviation provided a different signature for each of the three types of postural changes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of the heartbeat interval series from the subjects in the tilt-table study showed that the time courses of the mean R-R intervals and the heart rate series follow the well-documented patterns of cardiovascular response to orthostatic stress (7,16,25,26,46,50). Together, the instantaneous heart rate, instantaneous mean R-R interval, R-R standard deviation, and heart rate standard deviation provided a different signature for each of the three types of postural changes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). First, the time courses of the mean R-R intervals and the heart rate series follow the well documented patterns of cardiovascular response to orthostatic stress (Borst et al, 1982;Ewing et al, 1980;Heldt et al, 2002Heldt et al, ,2003Sprangers et al, 2003;Tanaka et al, 1995). In contrast, our heart rate variability series revealed a new pattern of temporal dynamics.…”
Section: Analysis Of Postural Changesmentioning
confidence: 99%
“…The tilt pairs are: rapid up (down) tilt in which the tilt table moved from horizontal (vertical) to vertical (horizontal) in less than 3 s; slow up (down) tilt in which the tilt table moved from horizontal (vertical) to vertical (horizontal) in approximately 1 min; and stand-up (supine) in which the subject stood up immediately supporting his or her own weight and then lied supine immediately from having been standing supporting his own weight (Heldt et al, 2002(Heldt et al, , 2003.…”
Section: Analysis Of Heart Beat Interval Dynamicsmentioning
confidence: 99%
“…The tilt-table test (see Figure 4.top.left) is a simple, noninvasive, and informative test first described in 1986 as a diagnostic tool for patients with syncope of unknown origin [Heldt et al, 2003]. Beyond diagnosing the condition, the test may reveal the cause, neurological disorder, metabolic disorder, mechanical heart disease, cardiac arrhythmias, etc.…”
Section: Case Study: Hemodynamicsmentioning
confidence: 99%